OP0003 Association between disease severity and onset of depression in knee osteoarthritis. (12th June 2018) - Rathbun, A.M.; Evans, Z.; Shardell, M.; Yau, M.; Gallo, J.; Stuart, E.; Schuler, M.; Hochberg, M.
Abstract : Background: Osteoarthritis (OA) is a heterogenous condition characterised by structural pathology of the joint and pain and disability that represent patients' experience of the illness. Disease progression may lead to deteriorating psychosocial health, but it is not clear what components of OA disease severity are related to depression onset in these patients. Objectives: The aim was to determine the components of OA disease severity that contribute to depression onset among individuals with radiographic knee OA. Methods: Eligible participants (n=1, 652) were from the Osteoarthritis Initiative with radiographic disease (Kellgren-Lawrence [K-L] grade 2, 3, or 4), complete baseline covariate data, and were below the screening threshold for probable depression (Centre for Epidemiological Studies Depression [CES-D] Scale≤16). OA disease severity was assessed at baseline and three annual follow-up visits using minimum joint space width (millimetres), 20-metre gait speed (metres per second), and pain subscale of the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). OA disease severity predictors were evaluated as a moving average at each time point then categorised in quintiles. Joint space width and gait speed categories were inverted so that increasing quintile corresponded to greater disease severity. Depression onset was assessed at four annual follow-up visits using the CES-D. Potential confounders included time-invariant and time-varying measures: demographics, lifestyle factors, socioeconomic status, Charlson comorbidity index, K-L grade, and WOMAC functional disability and joint stiffness; and CES-D score, body mass index, analgesic use, and knee injuries, respectively. Marginal structural models that account for time-dependent confounding and selective attrition modelled the association between each time-varying disease severity predictor and depression onset. Results: There was a non-linear probability (figure 1) for onset of depression by disease severity quintiles for the three predictors. Moreover, the risk of depression was greatest in the highest severity quintiles and reached statistical significance for all three predictors. Odd ratios comparing highest to lowest severity quintiles in order of increasing magnitude were 1.80 (95% confidence interval [CI]: 1.00, 3.24) for gait speed, 2.10 (95% CI: 1.17, 3.75) for joint space width, and 2.21 (95% CI: 1.14, 4.30) for pain. Conclusions: Findings demonstrate that the presence of greater structural disease severity and pain and decreased physical performance increases the risk of depression onset among individuals with radiographic knee OA. Thus, it is necessary to also intervene on OA disease severity when treating depression to effectively manage these patients. A combined treatment strategy consisting of two interventions delivered in parallel to simultaneously treat each condition may be the most effective form of medical care for OA patients who have comorbid depression. Acknowledgements: This study was supported by the Rheumatology Research Foundation's Scientist Development Award. Disclosure of Interest: A. Rathbun Grant/research support from: Rheumatology Research Foundation, Z. Evans: None declared, M. Shardell: None declared, M. Yau: None declared, J. Gallo: None declared, E. Stuart: None declared, M. Schuler: None declared, M. Hochberg: None declared